The Effect of Growth Mindset and Grit on Career Decision Making Self-Efficacy in Fresh Graduates - Ananda Apriliani Bulo; Abdul Azis (Universitas Ahmad Dahlan, 2024)
Indonesia is experiencing significant economic growth and industrial development. The role of fresh graduates in shaping and supporting this growth is crucial. However, unemployment remains a challenge, with 7.86 million people unemployed as of August 2023, and approximately 12% of them being bachelor’s and diploma graduates. The limited availability of jobs cannot keep pace with the growing number of job seekers, which increases with population growth each year. Students who possess a growth mindset, high levels of grit, and strong self-efficacy tend to achieve better learning outcomes, as these traits encourage continuous self-improvement and skill development. Consequently, researchers believe that a growth mindset and grit can significantly influence career decision-making self-efficacy, particularly among fresh graduates. This study employed a quantitative research approach with a correlational design. The sampling technique used was non-probability sampling. The sample size was determined using G*Power software, resulting in a minimum sample of 472 respondents. Three adapted measuring instruments were used in the study. The results indicate that growth mindset and grit positively impact career decision self-efficacy by 22.5%, while 77.5% is influenced by other factors. These findings confirm that growth mindset and grit play a significant role in career decision self-efficacy.